Elaboração de jaca passa por diferentes processos de secagem - Evaristo, Raquel Alves (2016)
The Brazilian fruit farming occupies a prominent place on the world stage, both the nutritional value and the importance of its derivatives. Tropical fruits are gaining ground because of its nutritional value, sensory characteristics, as well as the need to improve the population's quality of life, linked to aspects of health and well-being. The fruits of jackfruit (jackfruit Lam.) Are consumed in natura. Because of its taste and quite peculiar aroma, make it highly appreciated or rejected, and its high perishability leads to a high rate of post-harvest loss, causing losses to the producers of this fruit. Thus, the objective of this work was to determine the parameters of conventional and osmotic dehydration process, followed by drying at temperatures of 50 ° C and 60 ° C on the microbiological properties and physico-chemical assessment / sensory acceptability of jackfruit dehydrated (jackfruit-pass). It was observed that in conventional dewatering processes (DC), there was a weight loss greater, compared with osmotic dehydration processes followed by drying (OD), however, the time taken for completion of the process was higher compared to DC. Regarding the physicochemical analyzes the moisture content in dried jackfruit ranged from 36.23 to 17.47%; Ashes from 1.00 to 5.65%; pH 5.18 to 4.90; Acidity .60 to .17; soluble solids from 50.40 to 18.40 and water activity from 0.87 to 0.77 and carbohydrates ranged from 70.82 to 87.84% in the two temperatures used and applied in both cases. The final product has influences of the adopted treatments; there is the treatment of osmotic dehydration at a temperature of 50 ° C drying, which was considered ideal for the conditions under which the work was done by promoting greater acceptability of jackfruit passes in the analysis sensory.